Pharmacokinetics and Pharmacodynamics of Immediate- and Modified-Release Mycophenolic Acid Preparations in Healthy Beagle Dogs - Klotsman, Michael; Coquery, Sebastien; Sathyan, Gayatri; Naageshwaran, Vatsala; Shivanand, Paddy; Fairchild, Amanda J.; Garden, Oliver A.; Anderson, Wayne H. (Frontiers in Veterinary Science, 2021)
Background: Mycophenolic acid (MPA) is a broad-acting immunomodulating agent that may be therapeutically beneficial for the treatment of immune-mediated diseases in canine patients. Objectives: To determine the suppressive effects of MPA on T-lymphocyte proliferation, and to assess the feasibility of a dog-specific q24h modified-release MPA formulation (OKV-1001b). Animals: Fifteen healthy purpose-bred male beagle dogs. Methods: Two nearly identical open-label fifteen-day studies were conducted in which dogs were randomized to receive mycophenolate mofetil (MMF; 10 mg/kg q12h), or two doses of OKV-1001b (270 mg and 180 mg; q24h). Serial pharmacokinetic (PK) and pharmacodynamic (PD) samples were collected on Day 1, Day 8 and Day 15. MPA plasma concentrations were measured by LC-MS/MS, while an ex vivo lymphocyte proliferation assay was utilized for PD effects. Dogs were continuously monitored for evidence of side effects and gastrointestinal tolerability. Results: MPA induced inhibition of T-lymphocyte proliferation was observed following administration of all MPA preparations in a clear concentration-dependent manner. The PK/PD relationship was maintained across all days and time-points. Data generated herein suggest that MPA plasma concentrations above 600 ng/mL are sufficient to achieve at least 50% inhibition of T-cell proliferation. Conclusions and Clinical Importance: MPA holds therapeutic potential for treating dogs with immune-mediated disease, but clinical trials will be necessary to determine its safety and efficacy in naturally occurring disease. Likewise, q24h oral modified release MPA preparations that maintain MPA plasma concentrations between 600 ng/m and 1,000 ng/ml are warranted for further studies in client-owned dogs.